A new species of Eptesicus (Mammalia: Chiroptera: Vespertilionidae), from the sub-Andean Forest of Santa Cruz, Bolivia - Acosta S., Luis H.; Poma-Urey, José Luis; Ossa-López, Paula A.; Rivera-Páez, Fredy A.; Ramírez-Chaves, Héctor E. (THERYA, 2021)
Bats of genus Eptesicus are represented in South America by nine species of short-eared taxa (subgenus Eptesicus), and 10 species of long-eared species (subgenus Histiotus). Here we describe a new species of short-eared Eptesicus based on 19 specimens collected in the sub-Andean Bolivian-Tucumanian forest of Santa Cruz, between 1800-2020 masl. For this, we include morphological, morphometric, and molecular comparisons; we use principal component, discriminant function and mitochondrial genes (cytochrome-b, cytochrome c oxidase subunit I, and nicotinamide adenine dinucleotide dehydrogenase) to compare the new species with other taxa of the subgenus Eptesicus from South America. The new species is distinguished from its congeners by cranial shape, body measurements, and genetic distances. Furthermore, the new species is similar in cranial morphology to Eptesicus andinus but presents a highly developed frontal preorbital process, poorly developed in other related species (i. e., E. andinus, E. furinalis, and E. brasiliensis). All males were consistently darker than females in the new species. This taxon increases to 10 the number of species of bats of the subgenus Eptesicus in South America.